2021
DOI: 10.1002/adhm.202101239
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation‐Free Multilamellar Protein‐Lipid Hybrid Vesicles for Multifaceted Immune Responses

Abstract: Various lipid-based nanocarriers have been developed for the co-delivery of protein antigens with immunological adjuvants. However, their in vivo potency in vaccine delivery is limited by structural instability, which causes off-target delivery and low cross-presentation efficacies. Recent works employ covalent cross-linking to stabilize the lipid nanostructures, though the immunogenicity and side effects of chemically modified protein antigens and lipids can cause a long-lasting safety issue. Here robust "con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The hybrid vesicles coated with hydrophobic moleculeconjugated polymers also improved long-term stable circulation [16,17]. Recently, we reported that some oppositely charged globular proteins can induce the structural changes of pre-formed charged lipid nanovesicles into multilamellar structures through polyionic interaction under certain conditions [18,19]. Our approach is similar to nucleic acid-lipid ionic complexation, where negatively charged nucleic acids are intercalated into the interstitial space of cationic lipid vesicles to generate closely packed arrays through spontaneous phase conversion [20][21][22].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The hybrid vesicles coated with hydrophobic moleculeconjugated polymers also improved long-term stable circulation [16,17]. Recently, we reported that some oppositely charged globular proteins can induce the structural changes of pre-formed charged lipid nanovesicles into multilamellar structures through polyionic interaction under certain conditions [18,19]. Our approach is similar to nucleic acid-lipid ionic complexation, where negatively charged nucleic acids are intercalated into the interstitial space of cationic lipid vesicles to generate closely packed arrays through spontaneous phase conversion [20][21][22].…”
Section: Introductionmentioning
confidence: 88%
“…SAXS analysis was performed at the 4C SAXS II beamline at the Pohang Accelerator Laboratory (Pohang, Republic of Korea) [18,19]. The lipid particles were detected under 0.734 of X-ray beam wavelength with 2 m of sample-to-detector distance (SDD) for 10 sec at 25 o C. The magnitude of the scattering vector (q = (4π/λ)sinθ, θ = scattering angle) was determined between 0.01 Å -1 and 0.3 Å -1 .…”
Section: Small Angle X-ray Scattering (Saxs)mentioning
confidence: 99%
See 1 more Smart Citation
“…SAXS analysis was performed at the 4C SAXS II beamline at the Pohang Accelerator Laboratory (Pohang, Republic of Korea). , The lipid particles were detected under 0.734 of X-ray beam wavelength with 2 m of sample-to-detector distance (SDD) for 10 s at 25 °C. The q value ( q = (4π/λ)­sin θ, θ = scattering angle) was determined between 0.01 and 0.3 Å –1 .…”
Section: Methodsmentioning
confidence: 99%
“…16,17 Recently, we reported that some oppositely charged globular proteins can induce the structural changes of preformed charged lipid nanovesicles into multilamellar structures through polyionic interaction under certain conditions. 18,19 Our approach is similar to nucleic acid−lipid ionic complexation, where negatively charged nucleic acids are hybridized with cationic liposomes to generate nanovesicles through spontaneous phase conversion. 20−22 However, protein−lipid complexation is technically more challenging as the precise control of the intermolecular interaction between proteins and the lipid membranes of nanovesicles is complicated because of the low and heterogeneous surface charge density of proteins.…”
Section: Introductionmentioning
confidence: 99%